About Some Methods for Software Security - Mahmudova, Shafagat Jabrail (Discoveries in Agriculture and Food Sciences, 2019)
This study reviews software security, etc. It studies the methods for the analysis of software security. The problems of software protection are identified. The risks for software projects, their management, determination and categories are studied. Software development process includes the construction of an agreed structure for software development. The design of large distributed systems uses many programming languages, which in turn causes certain difficulties. That is, security in these cases is not provided. Software security is a set of measures aimed at its protection. Security in software exploitation is also a key issue. Software security is understood as its functioning without any problems. Information security threats arise in the process of software exploitation.